GAMBARAN PENGGUNAAN METODE KONTRASEPSI JANGKA PANJANG (MKJP) DI DESA LABOY JAYA WILAYAH KERJA UPT PUSKESMAS LABOY JAYA - Syukrianti Syahda; Fitri Apriyanti (Jurnal Maternitas Kebidanan, 2022)
Indonesia is a country with a relatively high population growth rate of 268,074,565 people. One of the efforts to suppress the rate of population growth is the Family Planning (KB) program. One method of contraception that is very appropriate to use in people who are classified as poor or poor is the Long-Term Contraceptive Method (MKJP).The Laboy Jaya sub-district is a sub-district in Kampar Regency, where the achievement rate for active family planning is still low, namely 62.3% of the total PUS. For the achievement of the use of contraceptives IUD 1.2%, AKBK 8.6%, MOW 0% and MOP 0%.The purpose of this study was to describe the use of MKJP in the working area of ​​the UPT Puskesmas Laboy Jaya. This research is quantitative descriptive with a descriptive cross-sectional study design. The population in this study were all family planning acceptors from January to November 2021 as many as 148 people with a total sample of 108 people. The sampling technique used is simple random sampling. The results obtained are that respondents who use MKJP are in the no-risk age category 21 people (33.3%), higher education 22 people (44.9%), working 25 people (42.4%) and multipara 28 people ( 34.1%). Meanwhile, respondents who used MKJP were in the category of being given family planning counseling, namely 25 people (53.2%). It is expected that respondents pneed moremore active in seeking information by participating in counseling conducted by the puskesmas regarding various contraceptives, side effects and how to use MKJP